ENRICHMENT OF LOGON BENTONITE AND ANALYSIS OF MODIFIED ORGANOBENTONITES USING SCANNING ELECTRON MICROSCOPY (Scientific journal of the Fergana State University, 2025)
This study investigates the effect of modifying bentonite with various surfactants on its morphological properties and elemental composition. Bentonite is a mineral with high adsorption capacity, and organic modification methods are used to improve its chemical and physical properties. In this research, bentonite samples were prepared and modified with surfactants such as tetradecyltrimethylammonium bromide (TDTMAB), octadecyltrimethylammonium bromide (ODTMAB), and dokocantrimethylammonium bromide (DKTMAB).The impact of modification on bentonite composition was evaluated using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). The results showed that modified samples exhibited changes in particle structure and a reduction in the degree of agglomeration. The increase in the hydrocarbon chain length of organic modifiers contributed to a more compact arrangement of bentonite particles and enhanced hydrophobic properties.The findings of this study help expand the applications of bentonite in various industries, including environmental purification, pharmaceuticals, and petrochemistry. It has been established that bentonite modification significantly improves its functional properties.